Interactive Control System Evaluation of Sekolah Dasar Pelangi in Responding Strategic Uncertainties of COVID-19 - Masayu Siti Aminah Qomariah; Emil Bachtiar (Budapest International Research and Critics University, 2022)
Sekolah Dasar Pelangi responded to instructions from the Government regarding increasing vigilance against the spread of COVID-19 as strategic uncertainties that could potentially thwart the implementation of the intended strategy, namely Project Based Learning. This study was aimed at evaluating the application of an interactive control system in the process of formulating a new emergent strategy for Sekolah Dasar Pelangiduring the COVID-19 pandemic. The approach used is a case study and qualitative research where the data will be obtained through in-depth interviews with the Institutional Management and the Principal of Sekolah Dasar Pelangi. Based on the results of the analysis, it is concluded that the process of formulating a new emergent strategy for Sekolah Dasar Pelangi uses an interactive control system at the initial stage of strategy formulation and evaluation of strategy implementation. A control system that focused on teaching infrastructure and teacher teaching skills is determined. Interactive meetings discuss data collected from the control system which is the focus of Sekolah Dasar Pelangi's strategic uncertainties and are used interactively. In the debates and dialogues, data on the development of the use of teaching infrastructure and the teaching skills of teachers became the focus of discussion and debate. The result of the debate and dialogue on the formulation of the new emergent learning strategy for Sekolah Dasar Pelangi is a learning strategy called Home Learning while still prioritizing the Project Based Learning learning design. At the evaluation stage, the interactive control system focus remains while in the debates and dialogues, survey data from parents and students were added after the implementation of the Home Learning learning strategy trial. The result is a new emergent strategy, namely Home Learning learning with a Project Based Learning design combined with pedagogical intelligence, social emotional, and enrichment.COVID-19; strategic uncertainties; interactive control system; debate and dialogue; intended strategy